Development of antioxidant gliadin particle stabilized Pickering high internal phase emulsions (HIPEs) as oral delivery systems and the in vitro digestion fate. Issue 2 (11th January 2018) - Zhou, F. Z.; Zeng, T.; Yin, S. W.; Tang, C. H.; Yuan, D. B.; Yang, X. Q.
Abstract : In this paper, we demonstrate for the first time the use of gliadin particles to structure algal oil (rich in DHA) and to exert chemical stability against lipid oxidation via the Pickering high internal phase emulsion (HIPE) strategy. Abstract : In this paper, we demonstrate for the first time the use of gliadin particles to structure algal oil (rich in DHA) and to exert chemical stability against lipid oxidation via the Pickering high internal phase emulsion (HIPE) strategy. The gliadin/chitosan colloid particles (GCCPs) were effectively adsorbed and anchored at the algal oil–water interface. Concomitantly, the particle-coated droplets as building blocks constructed a percolating 3D-network framework, endowing Pickering HIPEs with viscoelastic and self-supporting attributes. In addition, Pickering HIPEs loaded with shell (HIP-curEs) or core curcumin (HIPEs-cur) were constructed to depress the oxidation of algal oil. The content of primary (lipid hydroperoxides) and secondary (malondialdehyde and hexanal) oxidation products in HIPEs was lower than that in bulk oil. The oxidative stability of HIPEs was further improved in shell and core curcumin. An in vitro gastrointestinal (GI) model was constructed to characterize the lipid digestion, lipid oxidation as well as curcumin bioaccessibility of the ingested Pickering HIPEs. Lipid oxidation in the Pickering HIPEs was retarded under GI fluids, especially in the presence of core curcumin. The free fatty acid (FFA) fraction released was below 30% for all HIPEs, reflecting that the Pickering HIPEs formed restrict the digestion of fat or oil and potentially help to fight obesity. Interestingly, this route enhanced the bioaccessibility of curcumin from only 2.13% (bulk algal oil) to 53.61% (core curcumin); in particular, it reached 76.82% for shell curcumin. These results help to fill the gap between the physicochemical performance of the gliadin particle stabilized Pickering HIPEs and their potential applications as oral delivery systems of nutraceuticals. This work opens concomitantly an attractive strategy to convert liquid oils into antioxidant soft solids without artificial trans fats, as a potential alternative for PHOs.